The Influence Of E-Wallet Usage, Financial Literacy And Lifestyle On Financial Management Of Female Civil Servants In Mempawah District - Rachmanita Eza Putri Wiyandari; Nanda Wahyu Indah Kirana (UNIVED Press, 2024)
The Covid-19 pandemic has significantly accelerated the shift towards digital economy and digitization across various sectors, including Micro, Small, and Medium Enterprises (MSMEs). This article investigates the impact of digital technology integration on MSMEs' income post-pandemic. Through a study conducted in Mojokerto City, the findings indicate that the implementation of digital technology significantly contributes to the increase in MSMEs' income. Additionally, digital marketing strategies also have a significant impact on restoring MSMEs' income after the pandemic. These results provide a strong foundation for policymakers and business actors to enhance investments in digital technology and digital marketing strategies to improve the competitiveness and productivity of MSMEs in the future. Furthermore, age gap factors also play a crucial role in determining MSMEs' income levels post-pandemic. This article offers valuable insights for policymakers and MSMEs in planning more adaptive and effective strategies in the post-Covid-19 era. Thus, this research is not only relevant to MSMEs in Mojokerto City but also serves as an important reference for understanding the dynamics of the local economy post-pandemic in various regions